Skin‐associated lymphoid tissue could be a sign of systemic disease: reply from authors. (1st July 2021) - Kogame, T.; Kambe, N.; Takimoto‐Ito, R.; Nomura, T.; Kabashima, K.
Abstract: Linked Article:  Wang Br J Dermatol 2021; 185 :233 .